2018
DOI: 10.1002/zoo.21413
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biological factors on hematological and serum biochemistry values in captive Adélie, Chinstrap, Gentoo, and Macaroni penguins in Pingtung, Taiwan

Abstract: Hematology and serum biochemistry reference values are essential for health evaluation and disease diagnosis in penguins. However, there are currently no published physiological values for captive Adélie (Pygoscelis adeliae) and Chinstrap penguins (P. antarcticus), nor for wild or captive Macaroni penguins (Eudyptes chrysolophus). The present study is the first investigation regarding hematology and serum biochemistry reference values for captive Adélie, Gentoo (P. papua), Chinstrap, and Macaroni penguins in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…A study in wild nestling Rockhopper penguins (Eudyptes chrysocome) found no significant differences between males and females [31]. A study on captive Adélie, Chinstrap (Pygoscelis antarcticus), Gentoo (Pygoscelis papua), and Macaroni (Eudyptes chrysolophus) penguins in Taiwan found significantly lower values for mean corpuscular haemoglobin concentration (MCHC) and urea, higher values for Ca in females, a significant negative correlation with age for erythrocytes, lymphocytes, thrombocytes, AP, CK, LDH, and iron, and a significant positive correlation with age for mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), heterophiles, heterophile:lymphocyte ratios, ALT, and chloride [12]. The differences between the studies could have been influenced by the fact that the animals had different ages, were sampled at different locations, at different times, and are of different species and particularly by the fact that most previous studies are based on wild penguins, where many factors like health status and food intake are not exactly known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in wild nestling Rockhopper penguins (Eudyptes chrysocome) found no significant differences between males and females [31]. A study on captive Adélie, Chinstrap (Pygoscelis antarcticus), Gentoo (Pygoscelis papua), and Macaroni (Eudyptes chrysolophus) penguins in Taiwan found significantly lower values for mean corpuscular haemoglobin concentration (MCHC) and urea, higher values for Ca in females, a significant negative correlation with age for erythrocytes, lymphocytes, thrombocytes, AP, CK, LDH, and iron, and a significant positive correlation with age for mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), heterophiles, heterophile:lymphocyte ratios, ALT, and chloride [12]. The differences between the studies could have been influenced by the fact that the animals had different ages, were sampled at different locations, at different times, and are of different species and particularly by the fact that most previous studies are based on wild penguins, where many factors like health status and food intake are not exactly known.…”
Section: Discussionmentioning
confidence: 99%
“…A number of physiological factors can influence blood values in healthy animals. In penguins, studies have documented differences in various blood analytes depending on sex [10][11][12][13], age [12,14], body condition [13], time of day [15], season [13], year [14], location [13], and infection with malaria [16,17].…”
Section: Introductionmentioning
confidence: 99%